Analisis Perbandingan Kinerja Root Explorer Dan Oxygen Forensic Detective Pada Forensic Digital - Dwi Lestari, Yuyun; Fitri Annisah Lubis, Yessi; Akbar Siregar, Fadli (CV RIFAINSTITUT, 2023)
Rapid information and communication technology has a positive impact in the form of speed and ease of obtaining information and data by using an Android-based smartphone. But, on the other hand, it also has a negative impact in the form of cybercrime. This study aims to raise evidence of digital data and information in identifying pornographic crime cases using the Tantan app. The forensics analysis process in this study uses the National Institute of Justice (NIJ) method and 1 forensic tool, namely Oxygen Forensics Detective. The research scenario is the occurrence of pornography crimes. The research scenario is the occurrence of pornography crimes. This research succeeded in finding evidence in the form of photographs, videos, music, contacts, and chats. Testing using the Oxygen Forensic Detective tool, where the data taken on the Android pad uses the help of the Root Explorer application